Concepções de puérperas e profissionais de saúde de uma maternidade pública acerca da doação de leite materno. - Ludmilla Rodrigues Coelho Thomaz (2020)
Infant mortality is considered as one of the biggest problems of humanity. Moreover, complications of prematurity are some of the most challenging causes, due to its multifactorial aetiology and demands for intensive care in perinatal health. Among the care for preterm newborns (PTNB), nutrition is highlighted as a key factor related to survival and morbidities in these kids. When fed with the mothers' milk, PTNBs show better recovery when compared to other foods. Nutritional assistance considered as a “gold standard”, which in cases of justifiable impossibility, demands an alternative, with greater proximity to effectiveness. In this scenario, the performance of the Human Milk Banks is particularly relevant, especially regarding the sustainable supply of pasteurized breast milk. This is a great challenge, as it depends on donations from people who are able and aware of this cause. Thus, this study aims to understand the conceptions related to the donation of breast milk by health professionals and postpartum women in a public maternity hospital. Descriptive research, qualitative approach, involving 30 puerperal women and 52 health professionals. There were carried out individual interviews, transcribed and analyzed using thematic-strategic content analysis technique, with the aid of software, in light of the theoretical frameworks that supported the Health Humanization Policy, the Cegonha Network and non-medical practices in health. Three categories emerged, namely: (1) “Value of breast milk and human milk donation”, (2) “Health professionals' view on human milk donation” and (3) “Postpartum approach to milk donation “Breast milk”. There were learned conceptions with the potential to favour the donation of breast milk and then considered; and others that need to be (re) drawn to become potent, in strategies/projects to increase the donation of maternal milk, especially colostrum milk. As for the sense of colostrum breast milk, it was found concepts that were heavily permeated by biological aspects, especially by health professionals; also, the conceptions about the meaning of breast milk donation as an opening to a rich field of subjectivity. Regarding the health professionals 'views and practices, concerning the mobilization of mothers to donate breast milk, conceptions were revealed that, in general, need to be (re) signified, such as the subjects' autonomy and protagonism, co-responsibility among them, solidary bonds and collective participation in health practices that guide the National Humanization Policy - so that the donation of breast milk is a cross-cutting theme in the discussion of the construction of the maternity team, with participative management, aiming at welcoming the mothers for this donation. For that, health professionals need to feel or be in a team, in an interdisciplinary strategy for the donation of breast milk. Thus, it can be learned that this study presents relevant subsidies to improve the care and teaching processes, which are interlaced in the intervention practices of health professionals for the mobilization of mothers for the donation of breast milk, in an ethical-aesthetic-political understanding of work.